Ekstraksi Alumina (Al2O3) dari Mineral Tanah Napa Pesisir Selatan - Arinda Frissherly; Mawardi Mawardi (Jurnal Periodic Jurusan Kimia UNP, 2022)
Alumina has a wide range of industrial and technical applications and can be extracted from different locations, materials and methods. Napa soil from the South Coast has been used as a raw material for alumina production. This alumina extraction process is the result of modifications to several methods including alkali fusion and hydrothermal methods.Napa soil is calcined at 7500C for 4 hours and washed with hydrochloric acid 1,5 M; 2 M; 2.5 M at 950C, followed by alkali fusion by NaOH 10 M so that it is obtained Al(OH)3 and converted to Al2O3 with the calcination of 11000C. The extraction results are characterized by XRF technology to understand the content of the analyzed sample. The extraction mass of alumina with different concentrations of HCl 1 M; 1,5 M; 2 m; 2.5 M is continuous 14,171 g; 41,127 g; 31,711 g; and 0 g. The result of XRF analysis of alumina extraction showed that the Al2O3 content increased by 68.42%.